Effect of fruit dipping in hot water and cold storage duration on postharvest pear fruit characteristics. - Kasnazany, Sidiq Aziz Sidiq; Fatih, Avan Assi; Shekh-Marif, Hasan Shekh-Faraj (Sulaimani Journal for Pure and Applied Sciences, 2017)
Fruit samples of Harme Naska cultivar were subjected to hot water at 30°C and 50°C for 2 minutes after harvest and kept at 2 ±1°C in a cold room for 30 and 60 days in order to investigate the effects of hot water dipping and cold storage durations on some quality parameters (weight loss, total soluble solids, titratable acidity, fruit firmness, carotene, pectin and vitamin C contents). The main purpose of the study is to make some improvements in the previous properties and so the eating qualities would be better. Fruits dipped in 50°C for 2 minutes and cold stored for 60 days gave the highest water loss and carotene content while those dipped in tap water and cold stored for 30 days resulted in the greatest titratable acidity, fruit firmness and pectin content. No significant differences were observed for the effect of cold storage duration combined with hot water on total soluble solids while vitamin C content in the fruits was the most when they were dipped in various levels of hot water and cold stored for 30 days.
Keywords: Pear Fruit; Hot Water; Storage Duration; Fruit Quality